Skeletal maturity as injury risk factor in adolescent elite track and field athletes - Martinez Silván, D.; Johnson, A.; Tramullas, A. (Orthopaedic Journal of Sports Medicine, 2018)
Objectives: To establish skeletal age and maturity status in highly trained adolescent track and field athletes and to investigate the relationship between maturation status and different type of injuries. Methods: 72 adolescent track and field athletes from different athletic disciplines (long distance n=15, sprints n=16, jumps n=10, throws n=12, combined events n=9, non-specialized n=10) belonging to an elite sport academy full time between 2013 and 2016 were selected for the study. An electronic medical record for musculoskeletal injuries was designed according to international standards for athletics, and skeletal age and maturity status were determined at the beginning of each season using FELS method, athletes being defined as early matures (EM), late matures (LM) or normo-matures (Norm) according to the difference between chronological and skeletal age. Results: A total number of 195 injuries with an incidence of 7 injuries per 1000 h of training exposure were recorded in 72 athletes (15±1.7y, 169.5±9.9 cm, 61.4±17.9 kg, 215±64 training hours per season). A vast majority of athletes were early mature (EM=78%, Norm= 12%, LM= 10%). 98% of athletes in jumps, sprints, throws and combined events were EM, while a predominance of Norm (40%) and LM (40%) athletes was observed in the long distance group. A larger overuse injury incidence was observed in LM (4.1 inj/1000 h) and Norm (5.1 inj/1000 h) compared to early mature athletes (2.8 inj/1000 h). Apophysitis was the most common overuse injury, being significantly associated to maturation status (LM=4.1 inj/1000 h, Norm= 2.6 inj/1000 h, EM= 0.9 inj/1000 h; p<0.01), and long distance athletes the ones with a larger number of this kind of injuries (61%), and also with a larger training exposure (260 h per season). Conclusion: A predominance of late mature athletes was observed in long distance runners compared to all the other disciplines, and the risk of overuse injuries might increase when late mature athletes are exposed to large amounts of training during adolescence. Adapting training to maturation status and not to chronological age classical categories might reduce injury risk in adolescent track and field athletes.